Turning the Mirror on the Architects: A Study of the Open-Plan Office and Work Behaviors at an Architectural Company - Węziak-Białowolska, Dorota; Dong, Zhao; McNeely, Eileen (Frontiers in Psychology, 2018)
Following the rising cost of real estate and a desire to increase collaboration and communication among employees, the open-plan office has been trending over the past decades. Research about the impact of the open-plan office on humans is equivocal in endorsing this trend. The mixed results are further confounded following the specific job requirements, such as the need for privacy in jobs requiring a high level of concentration or, in contrast, the need for open workspace in jobs benefitting from team work and knowledge sharing. This study aims to understand the relationship between perceptions of three characteristics of the open-plan office (acoustical privacy, visual privacy, and office density), and the impact they yield on employees' judgment as well as affect-driven behaviors. The study benefits from the data from 456 employees located in 20 regional office locations within the same architectural firm. The restriction to employees of a design firm enables examinations of participants, who are already sensitive to the impacts of space by the nature of their work. The variables of interest included employee perception of the workspace (privacy, office density, and fit into workspace), employee rating of social relationships, self-reported mood (irritability) and optimal functioning (number of limited ability days), and work impacts (job satisfaction, work engagement, and job performance). The Model of behavior in an open-plan office setting based on affective events theory is adopted. Mediation roles of irritability and perception of fit into the workspace are examined. Structural equation modeling is applied to test the joint significance of the association between independent and dependent variables (direct effect) and the association between independent variables, mediator, and dependent variables (indirect effect). Nested structure of the data is accounted for by adjusting the standard errors for clustering. The significance of indirect and total effects is evaluated by the bootstrapping method. Our results show that working in the open-plan office limits the experience of privacy and intensifies the perception of intrusion among employees of an architectural company, mostly architects and designers. Additionally, employees' perception of lack of privacy and high office density negatively affect job satisfaction, work engagement, and internal work relation as well as increases the number of limited ability days. Interestingly, the lack of privacy and high office density seem to positively affect expressive personal relations among coworkers and job performance. We find supporting evidence for mediation roles of negative emotions, that is, irritability and perception of fit into the workspace.